2018
DOI: 10.1073/pnas.1811172115
|View full text |Cite
|
Sign up to set email alerts
|

Blood-derived plasminogen drives brain inflammation and plaque deposition in a mouse model of Alzheimer’s disease

Abstract: Two of the most predominant features of the Alzheimer’s disease (AD) brain are deposition of β-amyloid (Aβ) plaques and inflammation. The mechanism behind these pathologies remains unknown, but there is evidence to suggest that inflammation may predate the deposition of Aβ. Furthermore, immune activation is increasingly being recognized as a major contributor to the pathogenesis of the disease, and disorders involving systemic inflammation, such as infection, aging, obesity, atherosclerosis, diabetes, and depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 71 publications
4
54
0
Order By: Relevance
“…Aβ plays a role not only in in ammation but also in the coagulation cascade. There is an association between haemostatic factors and in ammatory mechanisms in AD [37]. In our study, we found an increase in plasminogen, brinogen and kininogen.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Aβ plays a role not only in in ammation but also in the coagulation cascade. There is an association between haemostatic factors and in ammatory mechanisms in AD [37]. In our study, we found an increase in plasminogen, brinogen and kininogen.…”
Section: Discussionsupporting
confidence: 65%
“…In our study, we found an increase in plasminogen, brinogen and kininogen. In AD, plasminogen was found to colocalize with Aβ plaques [37], while brinogen was capable of enhancing Aβ aggregation and brillization, causing impairment in AD [48,49]. Patients with higher levels of plasma brinogen and plasminogen modulating neuroin ammation had worsening cognitive decline and Aβ deposition [37,50,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, coagulation factor V, a central mediator of hemostasis, has been previously linked to delirium pathogenesis [33]. Further, plasminogen has been shown to potentiate neuroin ammation [86,87] and Alzheimer's disease-related pathology [86], and elevated serum kininogen has been associated with depression [85]. As with complement, our data suggest a relationship between POCD and dysregulation of these in ammatory and thromboactive factors.…”
Section: Discussionmentioning
confidence: 52%
“…There are two mechanisms related to the pathological process of AD: Aβ aggregation and activation of glial cells 11,12 . However, the causal relationship between the two needs to be further confirmed.…”
Section: Introductionmentioning
confidence: 99%